(untitled) (International Journal of Built Environment and Sustainability, 2016)
Urbanization tends bring out a number of problems, such as inadequate housing and urban services, increase land prices and construction costs, propagation of slums, pollution and deterioration of the urban environment. Currently, spatial development activities focusing on major cities of Sri Lanka are demanding urban infrastructure and services where municipalities are facing challenges on provision of the infrastructure and proper urban management too. This study seeks to identify the relevant criteria, indicators and a method for assessing the urban management performance of municipalities in Sri Lanka since specific measurement criteria and related indicators are not yet identified to evaluate urban management by the central government or local government levels. Based on Literature review, five criteria and 25 indicators were selected considering their applicability for the context of Sri Lanka. The Full Permutation Polygon Synthetic Indicator Method (FPPSI) was applied to synthesize indicators and the Synthetic indicator has been used to show the performance of each criterion in terms of urban service delivery. Colombo Municipal Council (CMC), Sri Jayawardenapura Kotte Municipal Council (SJKMC) and Moratuwa Municipal Council (MMC) have been selected as the case studies for this research. Although selected cases are within Colombo Metropolitan Region, none of the municipalities were achieved the “High” or “Very High” level of synthetic indicator (SR>= 0.50) that shows the standard of municipal service delivery of Sri Lanka as a whole. This research lays the platform to evaluate the functional performance of Municipal Councils to guide the future scenario and to make decisions at the grass root level for managing the urbanization related issues in the country. Also this research helps the government to know the current trends of development impact and to take necessary policy level decisions to guide the economic growth in a correct direction with the political manifestoes.